Deixis in the song lyrics of Adele's song - Arif Maulana; Fawwaz Rizky (English Journal Antartika, 2025)
This study examines deixis in the song lyrics of Adele using a qualitative approach, focusing on the types and pragmatic meanings of deictic expressions. The research is motivated by the importance of deixis in understanding how contextual meaning is constructed in song lyrics, particularly in Adele’s emotionally expressive and personal songwriting style. Deixis plays a crucial role in linking language to context, allowing listeners to interpret meaning beyond literal expressions. This study is significant because it contributes to pragmatic and linguistic analysis by highlighting how deictic expressions function as linguistic tools to convey emotional intimacy, perspective, and interpersonal relationships in contemporary song lyrics. The data were collected through purposive sampling from selected songs in Adele’s album 25, including Hello, All I Ask, When We Were Young, Love in the Dark, and Send My Love. The lyrics were carefully examined to identify deictic expressions, which were then classified based on Levinson’s (1983) theory of deixis, consisting of person, place, time, discourse, and social deixis. The interpretation of the data employed Yule’s (1996) pragmatic framework, emphasizing contextual meaning, speaker intention, and listener inference. The findings indicate that person deixis is the most dominant type, followed by temporal deixis, while spatial, discourse, and social deixis appear less frequently. These deictic forms reflect themes of emotional closeness, memory, longing, and self-reflection. The study concludes that deixis in Adele’s song lyrics functions as an essential pragmatic device that connects linguistic expression with emotional and contextual meaning, allowing personal experiences to be understood as shared and universal.